Creative Commons: a user guide - Aliprandi, Simone (Ledizioni, 2022)
Here is an operational manual which guides creators step by step in the world of Creative Commons licenses, the most famous and popular licenses for free distribution of intellectual products. Without neglecting useful conceptual clarifications, the author goes into technical details of the tools offered by Creative Commons, thus making them also understandable for total neophytes. This is a fundamental book for all those who are interested in the opencontent and copyleft world.